Association between early childhood outdoor activity and anxiety symptoms in preschoolers - Jian-Bo Wu; Yan Zhang; Yanni Yang; Shuang-Yan Qiu; Qiang Zhou; Jiemin Li; Jing-Yu Zhang; Danxia Xian; Fang Zhou; Ziyi Zhao; Yawei Guo; Yuying Zhang; et al. (BMC Psychiatry)
Abstract Background Recently, a decreasing trend has been observed in the frequency and duration of outdoor activity among children, which has garnered concern regarding the potential impacts of this decline during mental health in early childhood. Currently, the association between outdoor activity in early childhood and the symptoms of anxiety disorders in preschoolers remains unclear. The purpose of this study was to investigate the association between the frequency and duration of outdoor activity in children aged 0–1 and 1–3 years and anxiety symptoms in preschoolers. Methods A cross-sectional study was conducted in 2021 using questionnaires, included 69,571 preschoolers residing in Longhua District, Shenzhen. Data on family social demographics, outdoor activity frequency and duration in children aged 0–3 years, and the anxiety symptoms of preschoolers were collected through parent-completed questionnaires. Anxiety symptoms were measured using the Chinese version of the Spence Preschool Anxiety Scale (SPAS), which assesses symptoms across various dimensions. The association between early childhood outdoor activity and anxiety symptoms in preschoolers was analyzed using a binary logistic regression model. Results Children 0–1 years of age who were outdoors < 1 times/week had a higher risk of screening positive for anxiety symptoms in preschool age compared with children who were outdoors ≥ 7 times/week (OR = 2.55, 95% confidence interval(CI): 2.22–2.94). Children in this age group who were outdoors < 30 min/session had a higher risk of screening positive for anxiety symptoms in preschool age compared with children who were outdoors ≥ 120 min/ session (OR = 1.62, 95%CI: 1.38–1.90). Children 1–3 years of age, who were outdoors < 1 time/week had a higher risk of screening positive for anxiety symptoms in preschool age compared with children who were outdoors ≥ 7 times/week, (OR = 3.10, 95%CI: 2.72–3.54). Children in this age group who were outdoors for < 30 min/session had a higher risk of screening positive for anxiety symptoms in preschool age compared with children who were outdoors time ≥ 120 min/ session (OR = 2.07, 95%CI: 1.73–2.48). Conclusion Lower frequency and shorter duration of outdoor activity during infancy (0–1 and 1–3 years) had higher odds of screening positive for anxiety symptoms in preschoolers. A frequency of ≥ 7 outdoor activity per week and a duration of ≥ 120 min/session during infancy were associated with lower levels of anxiety symptoms in preschoolers.These findings provide actionable insights for parents and caregivers, highlighting the importance of promoting outdoor activity in early childhood care and parenting practices. Future studies should further explore the causal relationship between outdoor activity and the prevention of anxiety.